An Insurance Value Modeling Approach That Captures the Wider Value of a Novel Antimicrobial to Health Systems, Patients, and the Population - Mei S. Chan; Richard Holloway; Robert King; Rosie Polya; Rebecca Sloan; Jack C. Kowalik; Tom Ashfield; Luke S.P. Moore; Thomas Porter; Jonathan Pearson-Stuttard (Journal of Health Economics and Outcomes Research)
**Background:** Traditional health economic evaluations of antimicrobials currently underestimate their value to wider society. They can be supplemented by additional value elements including insurance value, which captures the value of an antimicrobial in preventing or mitigating impacts of adverse risk events. Despite being commonplace in other sectors, constituents of the impacts and approaches for estimating insurance value have not been investigated.